Seismic performance of reinforced concrete school in Sabah - Hamim, Sovester (2017)
One of the methods to evaluate the seismic performance is the nonlinear time history analysis. This is because the structural models are imposed to the real earthquake ground motion records. Current practice only considers single earthquake in the analysis. In reality, the earthquake tremors will occur repeatedly. This is known as multiple earthquakes. Ranau earthquake that occurred on 5 June 2015 also was not a single earthquake, but followed by several number of aftershock. This project is to investigate the performance of reinforced concrete (RC) school buildings in Sabah when subjected to multiple earthquakes. A total number of three models of school which have 2, 3 and 4 storeys has been used for the project. All models have been designed based on BS8110 to represent the existing RC school buildings. A total of seven ground motion for both single earthquake and multiple earthquakes have been considered in nonlinear time history analysis on all models by using SAP2000 program. All models are assumed to be located in moderate seismic region in Sabah, Malaysia. Objective of this work is to study the performance of RC school buildings in Sabah when subjected to multiple earthquakes. Based on a series of nonlinear time history analysis, this study concludes that the action of multiple earthquakes has contribute around 58% - 73% higher maximum lateral displacement compared to the single earthquake. This study also concludes that multiple earthquake significantly contributes around 60% - 67% higher interstorey drift ratio compared to the single earthquake. Thus, multiple earthquakes consideration should be taken in order to design new buildings as well as the evaluation for maintenance and rehabilitation of existing buildings.